p53 suppresses hyper-recombination by modulating BRCA1 function - Dong, Chao (DNA Repair (Amst), 2015)
Both p53 and BRCA1 are tumor suppressors and are involved in a number of cellular processes including cell cycle arrest, apoptosis, transcriptional regulation, and DNA damage repair. Some studies have suggested that the association of BRCA1 and p53 is required for transcriptional regulation of genes involved in cell replication and DNA repair pathways. However, the relationship between the two proteins in molecular mechanisms of DNA repair is still not clear. Therefore, we sought to determine whether there is a functional link between p53 and BRCA1 in DNA repair. Firstly, using a plasmid recombination substrate, pDR-GFP, integrated into the genome of breast cancer cell line MCF7, we have demonstrated that p53 suppressed Rad51-mediated hyper-recombinational repair by two independent cell models of HPV-E6 induced p53 inactivation and p53 knockdown assay. Our study further indicated that p53 mediated homologous recombination (HR) through inhibiting BRCA1 over-function via mechanism of transcription regulation in response to DNA repair. Since it was found p53 and BRCA1 existed in a protein complex, indicating both proteins may be associated at post-transcriptional level. Moreover, defective p53-induced hyper-recombination was associated with cell radioresistance and chromosomal stability, strongly supporting the involvement of p53 in the inhibition of hyper-recombination, which led to genetic stability and cellular function in response to DNA damage. In addition, it was found that p53 loss rescued BRCA1 deficiency via recovering HR and chromosomal stability, suggesting that p53 is also involved in the HR-inhibition independently of BRCA1. Thus, our data indicated that p53 was involved in inhibiting recombination by both BRCA1-dependent and -independent mechanisms, and there is a functional link between p53-suppression and BRCA1-promotion in regulation of HR activity at transcription level and possible post-transcription level.